A review of the common factors influencing e-records implementation in business organizations / Nurzeelawati Norolazmi, Irwan Kamaruddin Abd Kadir and Mohd Ridwan Seman@Kamarulzaman - Norolazmi, Nurzeelawati; Abd Kadir, Irwan Kamaruddin; Seman@Kamarulzaman, Ahmad Faris (Faculty of Information Management, 2022)
E-records have improved management and decision-making and easy to access information anywhere as well as to reduce the risk of information loss in business organizations. In a business organization, e-records are now very important for new developments and discoveries. E-records play an important role in ensuring effective service delivery and quality delivery in business organization. The purpose of this study is to review the common factors influencing erecords implementation among the business organizations based on literature review. This paper explores the factors on the adoption model for e-records implementation in business organizations by providing supportive evidence from existing research